Prevalence of hypervirulent Klebsiella pneumoniae strains in COVID-19 patients with bacterial co-infections - Zhang, Jingfen; Li, Qiaoyu; Liu, Jingjing; Fan, Fangfang; Shi, Yiwei; Yu, Xiao (Frontiers in Microbiology, 2025)
ObjectiveA recent alarming report from the World Health Organization highlighted the rapid global spread of a hypervirulent, carbapenem-resistant strain of Klebsiella pneumoniae. The COVID-19 pandemic frequently led to bacterial co-infections, with K. pneumoniae being a common and highly pathogenic agent. This study aimed to assess KP characteristics via whole-genome sequencing and clarify its molecular epidemiology to guide standardized clinical treatment.MethodsOur retrospective analysis of clinical data from COVID-19 patients admitted to our hospital between 7 December 2022, and 2 January 2023-following China’s policies changes, which led to a significant influx of patients-identified 17 K. pneumoniae isolates from sputum samples with bacterial co-infections. These isolates underwent whole-genome sequencing for ST typing, virulence gene annotation, plasmid profiling, and antimicrobial susceptibility testing.ResultsOf the 17 K. pneumoniae isolates, 52.9% were hypermucoviscous. Whole genome sequencing identified eight sequence types (STs), with ST23/KL1 being the most prevalent at 35.3%. Virulence genes were present in 94.1% of strains, including Yersiniabactin (70.6%), Aerobactin (82.3%), and Salmochelin (88.2%). Plasmid analysis revealed common IncHI1B/FIBk or IncFIBk types. All isolates were highly sensitive to antibiotics, except for blaSHV resistance. The 17 patients had a median age of 71 years and significant comorbidities, such as hypertension (64.7%) and diabetes (41.2%).ConclusionThe ST types and virulence gene profiles indicate that most K. pneumoniae strains co-infecting COVID-19 patients are common, high-virulence strains prevalent in the Asia-Pacific region. Our findings suggest that COVID-19 may contribute to the spread of hypervirulent K. pneumoniae strains, potentially informing the ongoing WHO epidemic alert.